RANCANGAN BANGUNAN IPAL AIR LINDI TPA CILOWONG MENGGUNAKAN INTEGRASI VSSF CONSTRUCTED WETLAND DAN FILTRASI ALAMI - FITRI DWIRANI; Ade Ariesmayana; Nila Prasetyo Artiwi; Deni Ihwanudin Firdaus (LPPM, 2026)
Leachate generated from municipal solid waste landfills contains various pollutants that may pose significant environmental risks if discharged without proper treatment. The increasing volume of waste and high rainfall intensity in tropical regions contribute to fluctuations in leachate quantity and quality, creating challenges for landfill management. This study aimed to design a leachate wastewater treatment plant (WWTP) for the Cilowong Landfill, Serang City, Indonesia, by integrating a Vertical Subsurface Flow Constructed Wetland (VSSF-CW) system with natural filtration units. The research employed a quantitative engineering design approach involving field observation, leachate characterization, hydrological analysis, rainfall frequency analysis, and hydraulic design calculations. Laboratory results showed that the average concentrations of Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) were 401.8 mg/L, 28.08 mg/L, and 765.6 mg/L, respectively. Hydrological analysis indicated that the maximum leachate discharge corresponding to a 10-year return period rainfall event reached 6,998.4 m³/day, while the average operational discharge was only 27.36 m³/day, highlighting the substantial influence of rainfall on leachate generation. Based on the design calculations, the proposed treatment system consists of an equalization basin with a volume of approximately 7,000 m³, a sedimentation basin of 600 m³, a constructed wetland unit of 260 m³, a filtration basin of 260 m³, and a separator basin of 130 m³. The integration of VSSF-CW and natural filtration is expected to enhance pollutant removal through sedimentation, adsorption, filtration, phytoremediation, and microbial degradation processes. The proposed design provides an environmentally friendly, cost-effective, and sustainable alternative for leachate treatment, particularly for landfills located in developing regions with tropical climatic conditions.